New vehicularities of the French language : exchanges between Turkey and French-speaking Africa. An opportunity for Galatasaray University students? - (:unkn) unknown (My University, 2020)
The article examines the new vehicularities of the French language brought about by the recent and rapid exchanges between Turkey and French-speaking Africa and questions the way in which they are considered in French language training at Galatasaray University. In this institution based on a Franco-Turkish cooperation agreement, the French language is closely linked to France. Deprived of guaranteed outlets in the Turkish context, the French language is more of symbolic interest to students than of real functional interest, which confers a certain fragility to the status of language of instruction. However, provided that the representations of the African Francophonie are taken into account, these new vehicles can help to give meaning to university training in the French language. The article is based on exploratory research that aims to lay the foundations for reflection, drawing on a set of data : synthesis of various available studies ; analysis of institutional documents and media discourse ; first exploratory interviews conducted with former graduates of Galatasaray University professionally engaged in exchanges between Turkey and French-speaking Africa.
Keywords: African Research